Istikhdamu Kitabi Tahriril Aqwali Litarqiyati Qudrati At-Thullabi ‘Alal Qawa'idi An-Nahwi - marhaban, ainal mawardah (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
Nahwu is material from learning materials taught in Arabic lessons and is also a very important material in Arabic. The success or failure of learning depends on various reasons including the methods and media used when teaching. So the purpose of this study is to find out how students' abilities in understanding Grammar. To find out whether the use of the book of tahrirul aqwal affects improving students' ability to understand rgrammaer. The approach used in this research is experimental research. The population and sample in this study were first-grade students (X MIA 2) at MAN 1 Aceh Tamiang. The instruments used in data collection were interviews and tests. The results of research on students' ability in learning grammar before using the book of tahrirul aqwal were very low, and after using the book of tahrirul aqwal it was very good. And the use of the book of tahrirul aqwal to improve students' ability to understand qawa'id nahwu has an effect.